Money as a symbol in the relationship between financial advisors and their clients: a dyadic study. Issue 4 (10th January 2022) - Lozza, Edoardo; Castiglioni, Cinzia; Bonanomi, Andrea; Poli, Federica
Abstract : Purpose: The paper aims to examine whether financial advisors can understand the symbols and meaning that investors associate with money and whether such ability plays any role in enhancing the advisor-investor relationship in terms of satisfaction, level of trust, referral propensity and loyalty. Design/methodology/approach: The authors used a dyadic research design. A total of 186 dyads of financial advisors and their clients took part in the study and completed two parallel self-administered questionnaires. Findings: The authors found that financial advisors often can detect the emotional associations that their clients attribute to money. Such ability can enhance their relationship with investors. Research limitations/implications: The main limitation of this study is its exploratory nature and the convenience sampling technique that was adopted. Therefore, researchers are encouraged to test the main findings further. Practical implications: The results have implications for the development of ad-hoc psychological training to enhance the relationship between financial advisors and investors. Understanding the symbolic meanings and the emotions that clients associate with money may be a prerequisite for a financial services company to succeed and be competitive in the sector. Originality/value: Despite acknowledging that money is not a neutral object but is layered with symbolic meanings and emotional associations, the behavioral finance literature has so far neglected to study these implications from either a theoretical or a practical point of view. This paper aims to fill this gap by investigating the symbolic value of money in the financial services industry.